(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The purpose of this study is to explore the relationship between Indian consumers’ ethnocentric tendency (CET) and consequent purchase behavior for domestic and foreign products. This research paper examines the relationships between CET and the behavioural outcomes of Indian consumers. The proposed hypotheses are tested for the CET-Consequent Behaviour Framework using the results of the survey of Indian consumers. Besides descriptive statistics, correlation coefficient and regression analysis were applied to examine the relationship between CET and consequent behavioural constructs. This study concludes that a significant relationship exists between consumer ethnocentrism and consequent purchase behavior (overall general purchase intention) for domestic and foreign products. The study has its implication for the domestic marketers as well as foreign marketers operating in India. While domestic firms can overplay the ethnocentric sentiments of Indian consumers in marketing their products, foreign firms have to plan peculiar entry and marketing strategies to deal with such sentiments.